2016
DOI: 10.1186/s12944-016-0310-8
|View full text |Cite
|
Sign up to set email alerts
|

The role of active brown adipose tissue (aBAT) in lipid metabolism in healthy Chinese adults

Abstract: BackgroundThe prevalence of dyslipidemia in China was increased over the last several years. Studies have shown that the activity of aBAT is related to the lipid metabolism. In this study, we analyzed blood lipid level in tumor-free healthy Chinese adults in order to determine the role of aBAT in lipid metabolism.MethodsWe retrospectively analyzed the factors that affect the blood lipid level in 717 tumor-free healthy adults who received blood lipid measurement and PET/CT scan by multivariate regression analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…The potential explanation may be that increased total energy and fat intake in humans was associated with spicy food intake. The type of dyslipidaemia (mainly hypertriacylglycerolaemia and low HDL-cholesterol) in Chinese adults is different from those in Western countries (mainly hypercholesteraemia and high LDL-cholesterol) ( 3 , 4 ) , probably because of low dietary fat and cholesterol intake and high carbohydrate intake in Chinese adults ( 4 ) . In contrast with meat being part of the staple food in a typical Western diet, plain and tasteless rice- or flour-based foods are staples for the Chinese population ( 55 ) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential explanation may be that increased total energy and fat intake in humans was associated with spicy food intake. The type of dyslipidaemia (mainly hypertriacylglycerolaemia and low HDL-cholesterol) in Chinese adults is different from those in Western countries (mainly hypercholesteraemia and high LDL-cholesterol) ( 3 , 4 ) , probably because of low dietary fat and cholesterol intake and high carbohydrate intake in Chinese adults ( 4 ) . In contrast with meat being part of the staple food in a typical Western diet, plain and tasteless rice- or flour-based foods are staples for the Chinese population ( 55 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Dyslipidaemia is one of the major risk factors in the pathogenesis of CVD ( 2 ) , often including hypercholesteraemia, hypertriacylglycerolaemia, high LDL-cholesterol and low HDL-cholesterol. Different from those in the USA and Europe, the main types of dyslipidaemia in Asian countries including China manifest as hypertriacylglycerolaemia and low HDL-cholesterol ( 3 , 4 ) . A report of the China National Diabetes and Metabolic Disorders Study from 2007–2008 estimated that 9·0 % (88·1 million) of Chinese adults had high total cholesterol (TC), 6·5 % (62·8 million) had high LDL-cholesterol and 22·3 % (214·9 million) had low HDL-cholesterol ( 5 ) .…”
mentioning
confidence: 99%
“…Thus, in rodents, metabolically active BAT exerts significant impact on circulating TRL metabolism. Lower plasma TG and increased HDL-c has been observed in subjects with metabolically active BAT determined by 18 FDG PET/CT ( 148 ). Experimental acute cold exposure in humans does not however lead to significant reduction in plasma TG levels ( 108 , 109 ) and may even lead to small increase in TG and cholesterol levels in some instances ( 106 , 141 ).…”
Section: Energy Substrates Utilization By Batmentioning
confidence: 99%
“…Importantly, diet and lifestyle factors are associated with the development of CKD and some of those factors are population-specific. Indeed, dyslipidemia among Chinese individuals is mainly manifested as high triglycerides and low HDL-C [2325], and this pattern has been associated, among other factors, with the high consumption of peppers [26]. Previous studies from Japan showed that high triglyceride and low HDL-C levels were associated with declining eGFR [2729].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, since CKD is related to environmental factors such as diet, stress, and population [21,22], population-specific studies are necessary to identify the factors adequately. The main manifestation of dyslipidemia in China is high triglycerides and low high-density lipoprotein cholesterol (HDL-C) levels [2325]. The Chinese diet has been associated with high blood triglycerides levels [26].…”
Section: Introductionmentioning
confidence: 99%